Primary Hyperparathyroidism in Older People: Surgical Treatment with Minimally Invasive Approaches and Outcome. (12th June 2012) - Dobrinja, Chiara; Silvestri, Marta; de Manzini, Nicolò
Abstract : Introduction . Elderly patients with primary hyperparathyroidism (pHPT) are often not referred to surgery because of their associated comorbidities that may increase surgical risk. The aim of the study was to review indications and results of minimally invasive approach parathyroidectomy in elderly patients to evaluate its impact on outcome. Materials and Methods . All patients of 70 years of age or older undergoing minimally approach parathyroidectomy at our Department from May 2005 to May 2011 were reviewed. Data collected included patients demographic information, biochemical pathology, time elapsed from pHPT diagnosis to surgical intervention, operative findings, complications, and results of postoperative biochemical studies. Results and Discussion . 37 patients were analysed. The average length of stay was 2.8 days. 11 patients were discharged within 24 hours after their operation. Morbidity included 6 transient symptomatic postoperative hypocalcemias while one patient developed a transient laryngeal nerve palsy. Time elapsed from pHPT diagnosis to first surgical visit evidences that the elderly patients were referred after their disease had progressed. Conclusions . Our data show that minimally invasive approach to parathyroid surgery seems to be safe and curative also in elderly patients with few associated risks because of combination of modern preoperative imaging, advances in surgical technique, and advances in anesthesia care.